Media Pembelajaran Dalam Pendidikan Agama Islam - Maisaroh Ritonga; Saripuddin Hasibuan; Saripah Aini Samosir; M Ali Ritonga; Abdul Latif Siregar (CV. ITTC INDONESIA, 2023)
To achieve the goals of Islamic education, in the learning process teachers should use learning media. By using learning media, teachers will more easily teach subject matter and students will more easily understand the lesson. The characteristics of Islamic learning media can be grouped into graphic media, audio media and silent projection media. Based on how it is obtained, media is differentiated based on the design and use of the media for the same purpose. When choosing media, you need to pay attention to the media selection criteria. By using media in the learning process, it is hoped that the quality of Islamic religious education will be even better